(3GdGROgGQ ajeG YbOg GdTYQGA ef GdBKGQs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3Pdc LRA LeYJ ajg GdCTYGQ GdJi YbO ajgG TjA ef GdCMGOjK hGdBKGQ s
(3BNQgG (B:s
(3Je cJGH GdGROgGQ ajeG YbOg GdTYQGA ef GdBKGQ HMeO Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: 7s
(3PcQ ai gOjI GdYGQajf HGdGSe GdeKHJ ai GdYfhGf GdCUdi(B: (3GdGROgGQ ajeG YbO GdTYQGA ef GdBKGQ (B535/1s
(3YdjgG hba ddLGeY GdCYXe GdecJHI GdCMeOjI HJhfSs
(3HJGQjN (B1256 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs